2020
DOI: 10.1111/lam.13380
|View full text |Cite
|
Sign up to set email alerts
|

Profiling the effects of physicochemical indexes on the microbial diversity and its aroma substances in pit mud

Abstract: Significance and Impact of the Study: Pit mud is a determining factor in the aroma of Baijiu. This study analysed the aroma substances, microbial composition and physicochemical indexes of pit mud in different years. So as to reveal the effects of physicochemical indexes on microbial communities and flavour substances. The results may provide a basis for studying the physicochemical indexes, community structure and flavour of Wenwang pits, offering a reference for optimizing the aroma and flavour of Baijiu.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 34 publications
0
29
0
Order By: Relevance
“…The microbiota of any environment or fermentation system is subject to the physicochemical factors of their surroundings, which is also the rationale for continuous domestication, enrichment and elimination of microorganisms in PM. Previous studies have consistently identified the pH of PM as the most influential and broad-ranging physicochemical factor on microbiota and a pivotal environmental stress role in the directed evolution of PM microbiota (Tao et al, 2014;Hu et al, 2016;Zhang M. et al, 2020). The pH of PM would significantly affect the reproduction of microorganisms and their involved biochemical reactions, and an appropriate pH could not only promote alcoholic fermentation, but also facilitate the formation of aroma precursors in SFB to improve product quality (Zhang M. et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The microbiota of any environment or fermentation system is subject to the physicochemical factors of their surroundings, which is also the rationale for continuous domestication, enrichment and elimination of microorganisms in PM. Previous studies have consistently identified the pH of PM as the most influential and broad-ranging physicochemical factor on microbiota and a pivotal environmental stress role in the directed evolution of PM microbiota (Tao et al, 2014;Hu et al, 2016;Zhang M. et al, 2020). The pH of PM would significantly affect the reproduction of microorganisms and their involved biochemical reactions, and an appropriate pH could not only promote alcoholic fermentation, but also facilitate the formation of aroma precursors in SFB to improve product quality (Zhang M. et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have consistently identified the pH of PM as the most influential and broad-ranging physicochemical factor on microbiota and a pivotal environmental stress role in the directed evolution of PM microbiota (Tao et al, 2014;Hu et al, 2016;Zhang M. et al, 2020). The pH of PM would significantly affect the reproduction of microorganisms and their involved biochemical reactions, and an appropriate pH could not only promote alcoholic fermentation, but also facilitate the formation of aroma precursors in SFB to improve product quality (Zhang M. et al, 2020). Interestingly, the present study found a very weak effect of pH on fungal communities in PM (Figure 6B).…”
Section: Discussionmentioning
confidence: 99%
“…Ethyl caproate ranks rst with respect to the content of esters, with its content in the pit mud from F-S, G-Z, H-X and I-D being 0.67%, 3.94%, 0.06% and 9.23% respectively. It is mainly generated under the synergistic action of various bacteria and enzymes [11] . Ethanol and acetic acid combine to form butyric acid, followed by the synthesis of caproic acid through esterase.…”
Section: Composition and Content Of Volatile Compounds In Pit Mudmentioning
confidence: 99%
“…Caproic acid and ethyl caproate produced by pit mud fermentation are the main aroma components of Taorong-type Baijiu [11] . A large amount of caproic acid is produced during fermentation, and then reacts with ethanol to produce ethyl caproate, the main aroma component of Baijiu [30] .…”
Section: Composition and Content Of Volatile Compounds In Pit Mudmentioning
confidence: 99%
See 1 more Smart Citation